2015
DOI: 10.1155/2015/468627
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Transcription Factor 7-Like 2 Risk Allele rs7903146 against Elevated Fasting Plasma Triglyceride in Type 2 Diabetes: A Meta-Analysis

Abstract: Background. The results from published studies regarding association of transcription factor 7-like 2 (TCF7L2) variant rs7903146 with dyslipidemia have been conflicting and inconclusive. Methods. We carried out a meta-analysis that aimed to investigate the association of the rs7903146 variant with plasma lipid levels using electronic database and published studies. Data was extracted by a standard algorithm. Dominant, recessive, homozygote, and heterozygote comparison models were utilized. Results. 24 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…This finding is in line with most of the previous studies, which found an association between the T allele and decreased β-cell function [12,13]. The T allele was also associated with lower baseline triglyceride levels in our study, which is again in accordance with the earlier studies [14]. Despite its known association with T2D, the T allele showed a protective effect against elevated fasting triglycerides in a large meta-analysis which included over 50,000 patients with T2D [14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in line with most of the previous studies, which found an association between the T allele and decreased β-cell function [12,13]. The T allele was also associated with lower baseline triglyceride levels in our study, which is again in accordance with the earlier studies [14]. Despite its known association with T2D, the T allele showed a protective effect against elevated fasting triglycerides in a large meta-analysis which included over 50,000 patients with T2D [14].…”
Section: Discussionsupporting
confidence: 93%
“…The T allele was also associated with lower baseline triglyceride levels in our study, which is again in accordance with the earlier studies [14]. Despite its known association with T2D, the T allele showed a protective effect against elevated fasting triglycerides in a large meta-analysis which included over 50,000 patients with T2D [14]. Although the mechanism for this is unknown, it is possible that TCF7L2 expression has opposite effects on plasma glucose and lipid levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the capacity of calcium-independent phosphate binders in reducing serum phosphate and limit arterial calcification while maintaining PTH levels in both preclinical and clinical CKD-MBD settings 132, 165 will very likely extend to diabetic patients with less severe 166 or no 167 renal insufficiency; this should be explicitly examined with consideration of the contextual modifiers discussed above. We must increasingly seek to exploit every opportunity to validate and vet our understanding of human vascular mineralized matrix metabolism – opportunities afforded by drug repurposing 10, 57, 103 , phase IV or similar studies 142 , and by coordinating human molecular genetics 164, 168 , metabolomics, and physiological phenotyping with preclinical model development 137, 168 . Not every approach will be successful.…”
Section: Translational Implications and Future Directionsmentioning
confidence: 99%
“…At baseline, we found that the TAG and cholesterol concentrations were lower in patients who carried one or two T alleles of rs79043146. Wang et al (26) reported in a metaanalysis that the minor allele (T) was associated with lower risk for hypertriacylglycerolaemia in subjects with type 2 diabetes, but no association was found between the minor (T) allele and plasma TC, LDL-cholesterol or HDL-cholesterol levels in subjects with type 2 diabetes or the metabolic syndrome. Ouhaibi-Djellouli et al (16) reported in a cross-sectional study with the InSulino-résistance à ORan (ISOR) population (non-T2DM subjects) that the T allele of the rs7903146 was associated with lower body weight (P = 0•02), lower BMI (P = 0•009), lower waist circumference (P = 0•01) and a lower waist:hip ratio (P = 0•02).…”
Section: Discussionmentioning
confidence: 99%